Neurotoxic effects associated with chronic inhalation and oral exposure to glyphosate-based herbicide IN adult rats - Bifaroni, Renata M.S.; Binotti, Giovanna D.; Bruneri, Karen P.; Tavares, Maria Eduarda A. [UNESP]; Ueda, Rose Meire R.; Rossi, Renata C.; Teixeira, Giovana R. [UNESP]; Corrêa, Camila Renata [UNESP]; Nai, Gisele Alborghetti (Oxford University Press (OUP), 2024)
The use of glyphosate-based herbicides (GBHs) for agricultural production has increased substantially around the world, as have their residues in the environment. Its effects on the central nervous system and neurotoxicity pathways are still not fully understood. The aim of this study was to evaluate the neurotoxic effect of chronic exposure to a GBH in adult rats. Sixty adult male albino Wistar rats were allocated into 6 groups, 2 control groups, and four GBH exposure groups (n = 10/group). The animals were exposed to two concentrations of GBH, orally and by inhalation: 2.99 × 10−3 grams of active ingredient per hectare (g.a.i./ha) and 7.48 × 10−3 g.a.i./ha. The animals were exposed for six months. Behavioral studies were performed. Brain tissue was collected for histopathological, immunohistochemical, and oxidative stress analyses. Animals exposed by inhalation to GBH spent more time in the central area of the open field test, whereas animals exposed to a high oral concentration of GBH spent less time in the open arms in the elevated plus-maze test. Tissue hyperemia occurred only in animals exposed to high concentrations of GBH. There was a greater thickness of the cerebral cortex and an increase in the expression of the BCL-2 in the animals exposed by inhalation to GBH. There was no difference in the doses of malonaldehyde and protein carbonylation between exposed and unexposed groups. The exposure to GBH caused increased levels of anxiety, regardless of the route, high concentrations caused hyperemia and inhalation exposure cause increased cortex thickness and increased BCl-2 expression.
Keywords: Chronic brain damage; Chronic toxicity; Occupational exposure; Pesticide exposure; Reactive oxygen species